MDCT and MRI in Genitourinary Imaging - Panebianco, Valeria. (A-Z Notes in Radiological Practice and Reporting, 2015)
The new series A-Z Notes in Radiological Practice and Reporting provides practical guides for residents and general radiologists, organized alphabetically, primarily according to disease or condition, permitting easy and fast consultation. All booklet are designed so as to cover a large spectrum of topics referring to different anatomical regions of interests. The present booklet offers a reliable assistance during the performance and reporting of multidetector row computed tomography and magnetic resonance imaging in patients with urogenital conditions. Entries typically include a short description of pathological and clinical characteristics, guidance on selection of the most appropriate imaging technique, a schematic review of potential diagnostic clues, and useful tips and tricks. Some helpful illustrations and schemes are also included.